Modulation of Caspase-3 Expression by Arcangelisia flava Post Acetaminophen-Induced Hepatotoxicity in Rat’s Liver - Steffi Liem; Tina Rostinawati; Ronny Lesmana; Sri Adi Sumiwi; Tiana Milanda; Mutakin Mutakin; Irma Melyani Puspitasari; Jutti Levita (The Prodia Education and Research Institute (PERI), 2018)
BACKGROUND: Acetaminophen, when used at low doses is a safe drug, but at higher doses it induces apoptosis in hepatoma cells. Arcangelisia flava that grows widely in Kalimantan Island, Indonesia, contains berberine which is effective in protecting the liver. This work was aimed to study the effect of A. flava extract on the modulation of caspase-3 in acetaminophen-induced hepatotoxicity.METHODS: Thirty-five Wistar male rats were divided into groups: I the normal control (water); II the negative control (Arabic gum powder or PGA, 2% in suspension); III the positive control (silymarin); IV-VII (A. flava extract 100, 200, 400, and 800 mg/Kg of body weight (BW), respectively) for 14 days. At day 15th, group II-VII were induced with acetaminophen 1000 mg/Kg of BW per oral for 7 days along with the extracts. At day 22nd, the animals were measured for their serum glutamic oxaloacetic transaminase (SGOT), serum glutamic pyruvic transaminase (SGPT) and gamma-glutamyl transferase (GGT), histological examination, and Western blotting.RESULTS: Acetaminophen elevated the SGOT and SGPT (3x compared to normal group), and GGT (5x compared to normal group) of the animals in group II. Pre-treatment with higher doses of A. flava extract (group VI and VII) significantly prevented the biochemical changes induced by acetaminophen. Normal histology of the liver was showed by group I, III, VII, whereas dilated sinusoids, central vein (CV) lesion, and local haemorrage were observed in group II, IV, V and VI. Western blotting showed an inhibition of caspase-3 expression by A. flava extract in dose-dependent manner.CONCLUSION: A. Higher dose A. flava extract shows hepatoprotective activity by preventing the elevation of serum transaminases and transferase levels. Eventually, no damage in the acetaminophen-induced rat’s liver was observed. This plant modulates the expression of caspase 3 protein in dose-dependent manner.KEYWORDS: Arcangelisia sp, caspase-3, berberine, hepatoprotective activity, NSAIDs, yellow root